Kajian Eksperimental Pengaruh Penggantian Sebagian Semen Dengan Limbah Las Karbit Pada Mortar - Dita Aninda; Putri Achir Wulansari; Muhammad Fajar A; Dianita Ratna Kusumastuti; Triwardaya Triwardaya (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2019)
The Development of residential facilities will affect the increase in needs of building materials.. Cement is one of the building materials whose raw materials come from nature. Availability of natural resources will affect the production of cement. Carbide welding waste is the remainder of the carbide reaction to water which produces acyetilene gas where 60% of the waste contains Calcium Oxide (CaO) which is the main constituent of cement. This study aims to analyze the effect of partial replacement of cement with carbide weld waste on mortar compressive strength. The study was conducted by making a mortar cube with dimensions of 5 cm x 5 cm x 5 cm with mixed proportions of 1PC: 3PS. Variation of partial replacement of cement with carbide welding waste used as much as 0%, 5%, 10%, 15%, and 20%. The results showed that the mortar compressive strength without carbide welding waste was used as the control variable, amounting to 329.33 kg/cm2. Mortar compressive strength with the proportion of partial replacement of cement with carbide welding waste 5%, 10%, 15%, and 20% respectively are 286.38 kg/cm2, 243.42 kg/cm2, 200.47 kg/cm2, and 157.51 kg/cm2. based on pengijuan results indicate that the mortar is included in type M at a proportion of a maximum of 15% with a compressive strength of 200.47 kg/cm2 according to the minimum requirements of 175 kg/cm2.